Distribution and assessment of marine debris in the deep Tyrrhenian Sea (NW Mediterranean Sea, Italy). Issue 1 (15th March 2015) - Angiolillo, Michela; Lorenzo, Bianca di; Farcomeni, Alessio; Bo, Marzia; Bavestrello, Giorgio; Santangelo, Giovanni; Cau, Angelo; Mastascusa, Vincenza; Cau, Alessandro; Sacco, Flavio; Canese, Simonepietro
Highlights: Deep rocky grounds of Tyrrhenian Sea were explored by means of ROV. Occurrence and abundance of submerged marine debris were described and quantified. Different degree of debris impact on benthic fauna were assessed. Fishing gears were the dominant source of debris in the deep Tyrrhenian Sea. Gorgonians and corals resulted to be the most impacted organisms by debris. Abstract: Marine debris is a recognized global ecological concern. Little is known about the extent of the problem in the Mediterranean Sea regarding litter distribution and its influence on deep rocky habitats. A quantitative assessment of debris present in the deep seafloor (30–300 m depth) was carried out in 26 areas off the coast of three Italian regions in the Tyrrhenian Sea, using a Remotely Operated Vehicle (ROV). The dominant type of debris (89%) was represented by fishing gears, mainly lines, while plastic objects were recorded only occasionally. Abundant quantities of gears were found on rocky banks in Sicily and Campania (0.09–0.12 debris m −2 ), proving intense fishing activity. Fifty-four percent of the recorded debris directly impacted benthic organisms, primarily gorgonians, followed by black corals and sponges. This work provides a first insight on the impact of marine debris in Mediterranean deep ecosystems and a valuable baseline for future comparisons.